RUSSIA AND AMERICA IN CENTRAL ASIA (An Attempt at Comparative Analysis) - PLASTUN, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2006)
At different times, the term “Central Asia” denoted different concepts depending on whether a geographer, politician, paleontologist, economist, historian, or linguist was using it. All of them, however, had to take into account the alignment of political forces responsible for the prevailing trends and developments. In the colonial period, Central Asia was known as “Sredniaia Azia,” term which applied to certain areas within czarist Russia and to certain republics within the Soviet Union’s borders. At one time, General Andrei Snesarev, an outstanding explorer of the region, wrote: “I regret to say that the very complicated developments in Central Asia were not investigated by scholars, impartial and sober interpreters of what they see, but primarily by politicians and nationalists who preferred to ignore objective reality and the way it affected the local context. They were looking for what they wanted to find, what was interpreted in their favor, and accepted their findings as the starting points for their political and military ventures. It was politics and political considerations that guided the studies of countries and people.”1 Indeed, as soon as England captured Hindustan, Central Asia became an area of Russian-English rivalry. The former expected the English to succumb to the temptation of conquering the seem ingly “no-man’s land” populated by the Central Asian Turks and to push on to Siberia. England, in turn, accused Russia of encroaching upon British possessions to gain access to the warm Indian Ocean. This doomed Afghanistan to the status of a buffer state for a long time to come. Its rulers tried independent policies: after routing two British military expeditions dispatched to subjugate the local tribes, the Afghan emirs began receiving huge sums of money from London in exchange for promised neutrality in the Russian-English rivalry. In turn, after conquering Central Asia (Turkestan) and failing to gain access to the warm seas, Russia dropped its intention. Stopped at the Pamirs, St. Petersburg was satisfied with Afghanistan’s neutrality. This was wise: tension in Europe was kept high by England and its allies, France and Turkey. In the 20th century, after the October 1917 Revolution in Russia, Central Asia lived in relative political equilibrium, which looked stable from Moscow. At first glance, the Soviet Central Asian republics were quite content with their status of “Soviet socialist republics,” while their leaders looked and sounded like devout Marxist-Leninists to the extent that they never hesitated to hail the not always wise economic decisions and struggle against “religious prejudices” suggested by Moscow and preferred to ignore the local ethnic problems. This impression was superficial: the presidents of the newly independent Central Asian states came from the former party elite of the Soviet Union. It turned out that the republican communist party bosses had always felt and acted as sovereigns of the vast lands Moscow entrusted to their power. The republics were ruled by clans; corruption and the shadow economy prevailed everywhere; industry and retail trade were used to make rich the local communist bosses who dutifully shared the spoils with their Moscow patrons.